(untitled) (Research, Society and Development, 2020)
In the present study, variations during storage were investigated in the postharvest quality of baby leaf of upland cress packed in different packages. The use of PET PCR packaging proved not to be feasible for the refrigerated storage of baby leaf of upland cress, whereas the zip lock packages of 100µm polyethylene and sealed 50µm low density polyethylene, proved to be good options. The experiment was then conducted using the zip lock packages of 100µm polyethylene and sealed 50µm low density polyethylene, under an average refrigeration temperature of 6ºC ± 1 and a relative humidity of 87% ± 1.6. The samples were evaluated at times 0, 2, 4, 6, 8, 10 and 12 days. The analyzes performed were percentage of mass loss, CO2 monitoring inside the packaging, color, pH, titratable acidity, total chlorophyll, total carotenoids, total phenolic content and antioxidant capacity. The 100µm polyethylene zip lock packaging determined less CO2 accumulation, greater preservation of green color, greater stabilization in the degradation of carotenoids and less depletion of the antioxidant capacity of the watercress baby leaf. These results suggest that the 100µm polyethylene zip lock packaging provides better storage conditions, giving the upland cress baby leaf a shelf life of up to 12 days, ensuring a quality product for the consumer.